Development of a Surface Plasmon Resonance and Fluorescence Imaging System for Biochemical Sensing - Lulu Zhang; Guijun Miao; Jing Zhang; Luyao Liu; Shisong Gong; Yichen Li; Dafu Cui; Yuanchen Wei; Duli Yu; Xianbo Qiu; Xing Chen (Micromachines, 2019)
Surface plasmon resonance (SPR) biosensors are an extremely sensitive optical technique used to detect the changes in refractive index occurring at the sensor interface. Fluorescence involves the emission of light by a substance that has absorbed light or other electromagnetic radiation, and the parameters of the absorbed and emitted radiation are used to identify the presence and the amount of specific molecules in a specimen. SPR biosensors and fluorescence analysis are both effective methods for real-time detection. The combination of these technologies would improve the quantitative detection sensitivity of fluorescence analysis and the specificity of SPR detection. We designed and developed an SPR and fluorescence synchronous detection system. The SPR module was based on two kinds of modulation methods, and the fluorescence module was capable of switching between four wavelengths. The fluorescence microspheres and A549 cells of different concentration were both detected by the SPR and fluorescence method synchronously in real time. The fluorescent signal and the optical signal of the SPR were shown to correlate. The correlation coefficient for fluorescent microspheres detection reached up to 0.9866. The system could be used in cell analysis and molecule diagnosis in the future.